1974
DOI: 10.1172/jci107676
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Free Fatty Acids as a Determinant of Myocardial Oxygen Consumption and Myocardial Ischemic Injury during Norepinephrine Infusion in Dogs

Abstract: A B S T R A C T Increased delivery of free fatty acids raises myocardial oxygen consumption (MV02) without influencing mechanical performance. The effects of norepinephrine on MV02 and on the size of ischemic injury after acute coronary occlusion were therefore studied before and during inhibition of lipolysis with P-pyridylcarbinol. In spite of similar mechanical responses to norepinephrine, MV02 increased by 57±11% before and significantly less, 31±6%, (P < 0.01) during inhibition of lipolysis. After coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(19 citation statements)
references
References 26 publications
0
17
0
2
Order By: Relevance
“…Since that time, many studies have assessed myocardial metabolism in vivo in animals and humans by measuring the chemical concentration of free fatty acids in the artery and coronary sinus (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The arterial-coronary sinus chemical differences suggested that free fatty acids (fatty acids bound to albumin) were the preferred myocardial substrate in the fasting, resting state.…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, many studies have assessed myocardial metabolism in vivo in animals and humans by measuring the chemical concentration of free fatty acids in the artery and coronary sinus (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The arterial-coronary sinus chemical differences suggested that free fatty acids (fatty acids bound to albumin) were the preferred myocardial substrate in the fasting, resting state.…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms have been discussed to explain this effect. In relative hypoxia, the higher expenditure of oxygen when fatty acids, not carbohydrates, are oxidized (3,14) might restrict the availability of oxygen to less cells than in the absence of fatty acids. Additionally, the inhibition of key enzymes or specific carriers (1,15,17,18,31), the induction of futile metabolic cycles (19) and, eventually, a direct physical "detergent-like" effect influencing cellular membrane stability (12) have been discussed to explain the deleterious effects of fatty acids on the hypoxic myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…Conditions whereby sympathetic tone is high (elevated catecholamines), such as during coronary artery bypass grafting (Kalman et al, 1995), acute myocardial ischemia (Oliver and Kurien, 1969;Maroko et al, 1971), and surgery (Hirvonen et al, 1978), are associated with elevated serum NEFA concentrations (Mjos et al, 1974;Lopaschuk et al, 1994), arrhythmias (Oliver and Kurien, 1969;Opie, 1988;Kalman et al, 1995), and left ventricular dysfunction (Henderson et al, 1970). Both arrhythmias and left ventricular dysfunction have been linked to elevated plasma NEFA concentrations (Henderson et al, 1970;Opie, 1988;Kalman et al, 1995) but a cause and effect relationship between the two remains tentative.…”
mentioning
confidence: 99%
“…Both arrhythmias and left ventricular dysfunction have been linked to elevated plasma NEFA concentrations (Henderson et al, 1970;Opie, 1988;Kalman et al, 1995) but a cause and effect relationship between the two remains tentative. Regardless, myocardial oxygen consump-tion (MVO 2 ) is elevated when tissue lipolysis (elevated free fatty acid concentrations) is stimulated by catecholamines (Mjos et al, 1974;Simonsen and Kjekshus, 1978), which could be undesirable in the oxygen-deprived myocardium. Thus, in the heart, under conditions of high sympathetic tone, especially when an imbalance between oxygen supply and demand is present, lowering circulating NEFA has the potential to be beneficial.…”
mentioning
confidence: 99%